An Incidental Finding of Heterotopic Pregnancy in a Patient Presented with acute Abdomen post D&C of Unwanted Pregnancy - Naghem Farouk, Abed; Mainul, Haque; Wisam Abdul Kadder, Yassin (2016)
Spontaneous heterotopic pregnancy is a rare condition. There is the simultaneous presence of intrauterine and extrauterine pregnancies. Such condition can be a life-threatening. The diagnosis can also be easily missed especially in early pregnancy. We present this case of a 28-year old patient who was misdiagnosed as normal intrauterine pregnancy. She had illegal termination of unwanted 14-week pregnancy in a private hospital. The patient presented to us with acute abdomen two days after D&C. Following clinical examination, uterine perforation was suspected. Abdominal ultrasound showed a coexisting abdominal pregnancy in the right hypochondrium. his heterotopic pregnancy was undiagnosed at her initial presentation to the first hospital. Emergency laparotomy was done, uterine perforation was sutured and abdominal pregnancy was excised.